2017
DOI: 10.1016/j.oret.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis Caused by Corynebacterium Species: Clinical Features, Antibiotic Susceptibility, and Treatment Outcomes

Abstract: Purpose To report the clinical features, antibiotic susceptibility profiles, treatment, and visual acuity (VA) outcomes of endophthalmitis caused by Corynebacterium species. Design Retrospective case series. Subjects Patients with endophthalmitis caused by Corynebacterium species. Methods Microbiology database records were retrospectively reviewed for all patients with endophthalmitis caused by Corynebacterium species from January 1, 1990 to December 31, 2012 at a large university referral center. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…They attributed this resistance to overuse of fluoroquinolones eye drops in the ophthalmology field. C. macginleyi is an opportunistic pathogen that causes several ocular infections, including conjunctivitis [ 7 , 8 , 18 ], corneal keratitis [ 17 , 19 ], glaucoma bleb-related infections [ 30 , 31 ], and endophthalmitis [ 10 , 29 ]. C. macginleyi can also cause non-ocular infections, such as bladder catheter infections [ 33 ], intravenous catheter infections [ 34 , 35 ], and septicemia [ 36 ].…”
Section: Corynebacterium Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…They attributed this resistance to overuse of fluoroquinolones eye drops in the ophthalmology field. C. macginleyi is an opportunistic pathogen that causes several ocular infections, including conjunctivitis [ 7 , 8 , 18 ], corneal keratitis [ 17 , 19 ], glaucoma bleb-related infections [ 30 , 31 ], and endophthalmitis [ 10 , 29 ]. C. macginleyi can also cause non-ocular infections, such as bladder catheter infections [ 33 ], intravenous catheter infections [ 34 , 35 ], and septicemia [ 36 ].…”
Section: Corynebacterium Speciesmentioning
confidence: 99%
“…The susceptibility of Corynebacterium to drugs varies depending on the species, according to published reports [ 7 , 8 , 9 , 10 , 14 , 16 , 18 , 19 , 21 , 22 , 23 , 27 , 28 , 32 , 53 , 54 , 57 , 58 , 59 , 60 ]. In the ophthalmology field, large clinical cohorts of Corynebacterium on the ocular surface have not yet been sufficiently studied.…”
Section: The Susceptibility Of Corynebacterium mentioning
confidence: 99%
See 1 more Smart Citation
“…Turicella otitidis classically shows good susceptibility to ß-lactams, vancomycin and fluoroquinolones [11,13]. Endophthalmitis due to Corynebacterium species in general has been shown to be susceptible to intravitreal vancomycin [6]. In this report, post-injection endophthalmitis secondary to Turicella otitidis appeared to be indolent in nature with a rapid response to empiric intravitreal vancomycin and ceftazidime.…”
Section: Discussionmentioning
confidence: 65%
“…Poorer clinical outcomes have been reported in post-anti-VEGF endophthalmitis associated with other species, particularly in Streptococcus species. Corynebacterium, a genus of gram positive bacilli or coccobacilli, is a rare cause of post-procedural endophthalmitis [5][6][7]. Corynebacterium was found in only about 1% of the Endophthalmitis Vitrectomy Study culture positive endophthalmitis cases [8] and has only rarely been reported after anti-VEGF injection [2].…”
Section: Introductionmentioning
confidence: 99%